2009
DOI: 10.1051/0004-6361/200811427
|View full text |Cite
|
Sign up to set email alerts
|

Rotational studies in the Orion Nebula Cluster: from solar mass stars to brown dwarfs

Abstract: Aims. Rotational studies at a variety of ages and masses are important for constraining the angular momentum evolution of young stellar objects (YSO). Of particular interest are the very low mass (VLM) stars and brown dwarfs (BDs), because of the significant lack of known rotational periods in that mass range. We aim to extend previous studies well down into the substellar regime, providing for the first time information on rotational periods for a large sample of young VLM stars and BDs. Methods. This extensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 56 publications
6
80
0
Order By: Relevance
“…More recently, Rebull et al (2006) and Cieza & Baliber (2007) find that in Orion and NGC 2264 stars with long periods are more likely than those with short periods to have IR excesses suggestive of disks. Very recently, Nguyen et al (2009) find in Taurus-Auriga and Chamaeleon I (∼2 Myr) that both accretors and non-accretors have similar distributions of v sin i, while Rodriguez-Ledesma et al (2009) confirm the result found by Herbst et al (2000Herbst et al ( , 2001Herbst et al ( , 2002 in ONC.…”
Section: Article Published By Edp Sciencessupporting
confidence: 65%
See 1 more Smart Citation
“…More recently, Rebull et al (2006) and Cieza & Baliber (2007) find that in Orion and NGC 2264 stars with long periods are more likely than those with short periods to have IR excesses suggestive of disks. Very recently, Nguyen et al (2009) find in Taurus-Auriga and Chamaeleon I (∼2 Myr) that both accretors and non-accretors have similar distributions of v sin i, while Rodriguez-Ledesma et al (2009) confirm the result found by Herbst et al (2000Herbst et al ( , 2001Herbst et al ( , 2002 in ONC.…”
Section: Article Published By Edp Sciencessupporting
confidence: 65%
“…In particular, as shown in Fig. 1, about 62% of our sample is almost inside the circle with radius equal to the so-called cluster radius (R cluster ;Hillenbrand 1997) where Rodriguez-Ledesma et al (2009) find an indication of higher P rot compared to the stars outside R cluster . This could indicate objects closer to the Trapezium center tend to rotate on average slower than the outer ones.…”
Section: Correlations With V Sin Imentioning
confidence: 64%
“…These flares may be the result of magnetic reconnections on the protostellar surface, which would produce radio flares on the timescales of minutes (e.g., Dulk 1985;Bower et al 2003;Forbrich et al 2008). Interactions between the magnetic fields of the protostar and its disk could also produce flares on the timescales similar to the rotation periods of young stars, which are typically days to weeks in the ONC (e.g., Shu et al 1997;Forbrich et al 2006;Rodríguez-Ledesma et al 2009). …”
Section: Variabilitymentioning
confidence: 99%
“…Whelan et al 2009), and are magnetically active showing evidence of rotational modulation of spots on their surface (e.g. Rodríguez-Ledesma et al 2009). It is therefore pertinent to ask whether brown dwarfs may also form and harbour planetary systems.…”
Section: Introductionmentioning
confidence: 99%